1996
DOI: 10.1093/qjmed/89.9.653
|View full text |Cite
|
Sign up to set email alerts
|

Clinical studies of multiple endocrine neoplasia type 1 (MEN1)

Abstract: Multiple endocrine neoplasia type 1 (MEN1) is an autosomal dominant disorder characterized by the combined occurrence of parathyroid, pancreatic islet and anterior pituitary tumours. To facilitate a screening programme for MEN1, we investigated 709 people (364 males and 345 females, age range 1-84 years) from 62 MEN1 families, and 36 non-familial MEN1 patients. Of those investigated, 220 (95 males and 125 females, age range 8-79 years) suffered from MEN1. Parathyroid, pancreatic and pituitary tumours occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
376
4
20

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 434 publications
(417 citation statements)
references
References 0 publications
17
376
4
20
Order By: Relevance
“…Foregut carcinoid tumors (thymic and bronchial), adrenocortical hyperplasia, multiple lipomas, facial angiofibromas, and skin collagenomas may also be seen in the syndrome. [1][2][3][4] Unusual features of MEN1-related tumors include their multiplicity, both within and among target organs, and an earlier age of onset than similar sporadic tumors. 5 Symptoms in MEN1 are caused by an overproduction of specific hormones, neoplasm mass effects, or malignant transformation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Foregut carcinoid tumors (thymic and bronchial), adrenocortical hyperplasia, multiple lipomas, facial angiofibromas, and skin collagenomas may also be seen in the syndrome. [1][2][3][4] Unusual features of MEN1-related tumors include their multiplicity, both within and among target organs, and an earlier age of onset than similar sporadic tumors. 5 Symptoms in MEN1 are caused by an overproduction of specific hormones, neoplasm mass effects, or malignant transformation.…”
mentioning
confidence: 99%
“…Clinical disease is uncommon before 10 years of age. 1,3,8 The MEN1 gene, located at chromosome 11q13, is approximately 9.8 kb in length and contains 10 exons. The 1830-bp coding region in exons 2 to 10 generates a 610 amino acid protein of unknown function called "menin."…”
mentioning
confidence: 99%
“…On the other hand, it has recently been reported that a Japanese patient with FHP had a germline mutation of the MEN1 gene (Y353X in exon 8), although the clinical evaluation for MEN1 was not described in this family [13]. Primary hyperparathyroidism is usually expressed at an early age (85% by age 35) and has a high penetrance (95%) in MEN1 [14]. Patients with MEN1 may initially have primary hyperparathyroidism as the only manifestation of their disease and therefore, are difficult to distinguish from patients with primary hyperparathyroidism without MEN1.…”
Section: Discussionmentioning
confidence: 90%
“…Our index patient presented with assumed PHPT, which is typically the first manifestation of MEN1 and occurs in 95% of cases 18, 19. In addition, he had a NET (formerly known as carcinoid), which have been reported to occur in 4% of MEN1 patients 16, 19, 20. In retrospect, the clinical MEN1 diagnosis was not clear‐cut, with several lines of evidence suggesting that our index patient was most likely a so‐called phenocopy, that is, a phenotype resembling MEN1 without being it 21, 22.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, the patient was negative for all mutations known to cause MEN1, although about 5–15% of considered MEN1 cases are genetically unverified 17, 23, 24. Furthermore, only the index patient had affection of more than one organ, and as the penetrance of MEN1 is close to 100% in patients older than 50 years, it is unlikely that the 71‐year‐old father should be unaffected 20, 25. The low CCCR is also not typical for PHPT, but can occur due to low vitamin D. According to Thakker et al, MEN1 phenocopies are seen in up to 10% of cases with the causative mutations found in other genes including CDC73 and CASR .…”
Section: Discussionmentioning
confidence: 99%